Toxic effects of chemical warfare agent mixtures on the mussel Mytilus trossulus in the Baltic Sea: A laboratory exposure study. (March 2019) - Höher, Nicole; Turja, Raisa; Brenner, Matthias; Nyholm, Jenny Rattfelt; Östin, Anders; Leffler, Per; Butrimavičienė, Laura; Baršienė, Janina; Halme, Mia; Karjalainen, Maaret; Niemikoski, Hanna; Vanninen, Paula; et al.
Abstract: Baltic blue mussels ( Mytilus trossulus ) were implemented to assess potential toxicity, health impairments and bioaccumulation of dumped chemical warfare agents on marine benthic organisms. Mussels were collected from a pristine cultivation side and exposed under laboratory conditions to different mixtures of chemical warfare agents (CWAs) related phenyl arsenic compounds, Clark I and Adamsite as well as chloroacetophenone. Using a multi-biomarker approach, mussels were assessed thereafter for effects at different organisational levels ranging from geno-to cytotoxic effects, differences in enzyme kinetics and immunological responses. In an integrated approach, chemical analysis of water and tissue of the test organisms was performed in parallel. The results show clearly that exposed mussels bioaccumulate the oxidized forms of chemical warfare agents Clark I, Adamsite (DAox and DMox) and, to a certain extent, also chloroacetophenone into their tissues. Adverse effects in the test organisms at subcellular and functional level, including cytotoxic, immunotoxic and oxidative stress effects were visible. These acute effects occurred even at the lowest test concentration. Highlights: First study proving bioaccumulation of oxidized CWAs into marine organisms. Impairments on mussels by oxidized CWAs at the subcellular and functional level. Effects occurred even at lowest exposure concentrations.